Pengaruh Konsentrasi Kinetin dan NAA Terhadap Perbanyakan Tanaman Jeruk Kisar Secara In Vitro - Lawalata, Imelda J; Manuputty, Ariance; Raharjo, Simon H T (JURNAL BUDIDAYA PERTANIAN, 2021)
‘Kisar’ orange is one of oranges from ‘Kisar’ Island, Southwest Maluku District. Optimizing media composition for orange micropropagation is indispensable to enhance propagation or multiplication ability and seedling quality. This research aimed to study the effect of combination of plant growth of shoots of ‘Kisar’ orange and get the optimal combination. The research material were ‘Kisar’ orange explants from previous shoot cultures on MS medium. The materials for this study were explants of Kisar orange that were previously subculttured on MS medium. This descriptive study involved the use of combination of four treatment levels of kinetin and NAA consentrations,with three replication treatments of kinetin and NAA, consisting of 0,00 µM (control), 0,50 µM, 0,75 µM and 1,00 µM. The results showed that kinetin and NAA treatments in the in vitro culture medium gave different effects on shoot growth of ‘Kisar’ orange. The combination 1,00 µM kinetin and 1,00 µM NAA was the best combination for in vitro shoot growth of ‘Kisar’ orange, while the combination of 1,00 µM kinetin and 0,50 µM NAA was the best for the number of internodes and leaves, and medium with 0.00 µM kinetin and 0.75 µM was the best for explant height.